Review Artikel : Hubungan Pemberian Imunisasi Bcg Terhadap Penyakit Tuberkulosis Pada Anak - Tintia Rafika Putri; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Tuberculosis is a disease that often attacks humans, especially children or infants, and tuberculosis is one of the highest causes of death in the world, Indonesia ranks second as the country with the most tuberculosis cases in the world. Tuberculosis is often called an infectious disease that is easily transmitted between humans, and tuberculosis is caused by the bacterium Mycobacterium tuberculosis. This research was conducted through a library study in October 2022 through descriptive analysis and found the results that BCG immunization cannot cure TB but can prevent or reduce the risk of developing tuberculosis. The Mycobacterium bovine bacteria contained in the BCG immunization trigger the immune system to produce cells that can protect against the bacteria that cause tuberculosis. Therefore, giving immunizations to children is very much considered by parents and health workers so that children are not easily infected with the bacteria that cause tuberculosis, and health workers are advised to increase immunization programs and control patients with complaints of children's lung disease so that disease transmission does not occur.